PENGEMBANGAN MEDIA “GALERI AKSARA” UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR DALAM PEMBELAJARAN BAHASA INDONESIA - Nethania, Ruth; Kencana Sari, Fransiska Faberta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' beginning reading ability is currently low, marked by a gap between the expected end-of-semester achievement and students' mastery of letters, syllables, and basic words, largely because the teaching media used are still limited to the whiteboard and lecturing method. This research and development study aims to describe the development process of the “Galeri Aksara” learning media and to analyze its validity, practicality, and effectiveness in improving the beginning reading ability of first-grade elementary school students in Indonesian language learning. The study used the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). “Galeri Aksara” is a physical (non-digital) educational tool made of acrylic, consisting of a letter-card area, a word-arrangement grid area, and a picture area. The product was tested on a limited basis on 15 first-grade students at SD Negeri Tegalrejo 05. Data were collected through expert validation sheets, a student response questionnaire, and a beginning reading test, then analyzed quantitatively. The results show that the media is categorized as very valid, with a material-expert validation score of 80% and a media-expert score of 96%. The paired-sample t-test showed a significant difference between the pretest (mean 48.20) and posttest (mean 79.13) scores, Sig. (2-tailed) = 0.000, with an average N-Gain of 0.5945 (59.45%), classified as moderate. The student response questionnaire produced an average practicality score of 74.9, categorized as good. These findings indicate that “Galeri Aksara” is valid, practical, and effective for improving beginning reading skills. Keywords: Galeri Aksara media, beginning reading ability, ADDIE, Research and Development, elementary school